UJI AKTIVITAS ANTIBAKTERI SEDIAAN SABUN PADAT EKSTRAK ETANOL KULIT JERUK BALI (Citrus maxima) TERHADAP BAKTERI Staphylococcus aureus DAN Pseudomonas aeruginosa - Putra, Teguh Adiyas; Ulfah, Mariam; Ayu Syarifah, Nyimas (Sam Ratulangi University, 2024)
Grapefruit (Citrus maxima) has antibacterial activity mostly located in the peel. Compounds that are antibacterial in grapefruit peel (Citrus maxima) are flavonoids. The purpose of this study was to determine the best concentration of solid soap preparations of ethanol extract of grapefruit peel (Citrus maxima) that can inhibit the growth of Staphylococcus aureus and Pseudomonas aeruginosa bacteria. The method used is maceration by soaking simplisia in 96% ethanol for 1x24 hours then concentrated with a rotary evaporator and then evaporated with a watter bath. The finished extract was tested for phytochemical compounds of alkaloids, flavonoids, saponins and tannins. Then thin layer chromatography was carried out to emphasize flavonoid compounds. Then solid soap preparations were made with extract concentrations F1 5%, F2 7%, and F3 9%, then preparation evaluations were carried out such as organoleptic tests, homogeneity, pH, foam stability and cleaning power. After that, the antibacterial test was carried out using the disc method. The results of the diameter of the inhibition zone of the best Staphylococcus aureus antibacterial test were F3 9% concentration, which was 2.6 cm. While for Pseudomonas aeruginosa bacteria with 9% F3 concentration is also the best with an inhibition zone diameter of 1.3cm.